212k views
1 vote
Witch expression represents the composition g(f(x)) for the functions below? F(x)=-3x^2 g(x)=3x

User Hurelu
by
5.0k points

2 Answers

3 votes

Answer:

-9x²

Explanation:

We have given two functions.

We have to find their composition.

f(x) = -3x² and g(x) = 3x

(gof)(x) = g(f(x)) = ?

Firstly , we have to put the value of f(x) in g(f(x)).

Putting given values, we have

g(f(x)) = g(-3x²)

g(f(x)) = 3(-3x²)

g(f(x)) = -9x² which is the answer.

User Hernaldo Gonzalez
by
4.9k points
3 votes

Answer:


-9x^2

Explanation:

Composition of two functions can be obtained by replacing inner function in place of x of outer function and then plugging back the actual value of inner function f(x) and then simplifying it gives g(f(x)) which is usually called gof(x) .

f(x) = -
-3x^2

g(x) = 3x

g(f(x) ) = 3 f(x)

=3 (
-3x^2)

=
-9x^2

User Sothy Lorn
by
5.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.